Plant competition cues activate a singlet oxygen signaling pathway in Arabidopsis thaliana - Berardi, Nicole; Amirsadeghi, Sasan; Swanton, Clarence J. (Frontiers in Plant Science, 2024)
Oxidative stress responses of Arabidopsis to reflected low red to far-red signals (R:FR ≈ 0.3) generated by neighbouring weeds or an artificial source of FR light were compared with a weedfree control (R:FR ≈1.6). In the low R:FR treatments, induction of the shade avoidance responses (SAR) coincided with increased leaf production of singlet oxygen ( 1 O2). This 1 O2 increase was not due to protochlorophyllide accumulation and did not cause cell death. Chemical treatments, however, with 5-aminolevulinic acid (the precursor of tetrapyrrole biosynthesis) and glutathione (a quinone A reductant) enhanced cell death and growth inhibition. RNA sequencing revealed that transcriptome responses to the reflected low R:FR light treatments minimally resembled previously known Arabidopsis 1 O2 generating systems that rapidly generate 1 O2 following a dark to light transfer. The upregulation of only a few early 1 O2 responsive genes (6 out of 1931) in the reflected low R:FR treatments suggested specificity of the 1 O2 signaling. Moreover, increased expression of two enzyme genes, the SULFOTRANSFERASE ST2A (ST2a) and the early 1 O2responsive IAA-LEUCINE RESISTANCE (ILR)-LIKE6 (ILL6), which negatively regulate jasmonate level, suggested that repression of bioactive JAs may promote the shade avoidance (versus defense) and 1 O2 acclimation (versus cell death) responses to neighbouring weeds.†Nicole Berardi and Sasan Amirsadeghi contributed equally to this work.